2020
DOI: 10.3389/fsufs.2020.566345
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Climate Resilience of Rain-Fed Potato Through Legume Intercropping and Silicon Application

Abstract: A large portion of sub-Saharan Africa is situated in belts of uncertain rainfall and are characterized by low soil fertility with limited capacity to adapt to and mitigate the impacts of climate change. A field study was conducted in the semi-humid potato-growing belt of Kenya to test the effect of legume intercropping and water soluble silicon (orthocilicic acid) on soil erosion, and use efficiency of light and water. Potato (Solanum tuberosum L.) was grown singly and intercropped with dolichos (Lablab purpur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 56 publications
1
20
2
Order By: Relevance
“…Thus, this study was carried out to evaluate the effects of Si on the plant growth traits in response to an increasing level of NH + 4 supply, to unveil the associated mechanisms that are responsible for the alleviatory role of Si on NH + 4 toxicity in cabbage. Several studies have shown that the application of Si could remarkably promote the plant growth and development, oscillating from crops to vegetables (Savant et al, 1996;Khan et al, 2015;Nyawade et al, 2020;Da Silva et al, 2021). In our trials, the cabbage shoot and root growth were also enhanced to varying extents by the supplementation of Si.…”
Section: Discussionsupporting
confidence: 59%
“…Thus, this study was carried out to evaluate the effects of Si on the plant growth traits in response to an increasing level of NH + 4 supply, to unveil the associated mechanisms that are responsible for the alleviatory role of Si on NH + 4 toxicity in cabbage. Several studies have shown that the application of Si could remarkably promote the plant growth and development, oscillating from crops to vegetables (Savant et al, 1996;Khan et al, 2015;Nyawade et al, 2020;Da Silva et al, 2021). In our trials, the cabbage shoot and root growth were also enhanced to varying extents by the supplementation of Si.…”
Section: Discussionsupporting
confidence: 59%
“…That is, under intercropping, there was an increase in per-plant coffee production by 8% (on overall average). Intercropping with taller trees is reported to reduce excessive solar radiation and wind damage (Pezzopane et al, 2010;Rigal, Xu, Hu, et al, 2020), decreasing the temperature and creating a favorable microclimate for coffee during the warmest periods of the year (Araújo et al, 2016;Carr, 2001;DaMatta, 2004;Rigal, Xu, Hu, et al, 2020;Steiman et al, 2011), which mitigate water losses by transpiration and reduce stomatal closure (van Kanten & Vaast, 2006;Mariño, 2014;Nyawade et al, 2019Nyawade et al, , 2020Rigal, Xu, Hu, et al, 2020). However, the benefits of intercropping on per-plant coffee production were not realized under irrigation, with an evenly distributed reduction of 8% over the years.…”
Section: Competition Indices Under the Intercropping System And Diffe...mentioning
confidence: 99%
“…Under intercropping, crops can achieve a more effective complementarity in the use of environmental resources such as land (Gitari et al, 2020; Maitra et al, 2020; Mead & Willey, 1980), nutrients (Gao et al, 2014; Mei et al, 2012), water (Meixiu et al, 2020; Ren et al, 2016; Rezig et al, 2013; Wang et al, 2015, 2020), and light (Raza et al, 2019; Wang et al, 2015), especially when there is a temporal and spatial exploration of these resources (Brooker et al, 2014; Dong et al, 2018; Duchene et al, 2017; Glaze‐Corcoran et al, 2020; Nyawade et al, 2020; Raza et al, 2021; Rigal et al, 2020; Rigal et al, 2020). Although several studies have found a reduction in coffee yield when grown under intercropping with trees (Araújo et al, 2016; Rigal, Xu, Hu, et al, 2020; Rigal, Xu, & Vaast, 2020; Snoeck et al, 2013; Steiman et al, 2011), recent research has demonstrated that depending on the companion tree species used and their spatial arrangement, intercropping of the Arabica coffee can be quite efficient (Perdoná & Soratto, 2015b, 2016, 2020; Rigal, Xu, Hu, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The cropping systems with a more intense focus on raising of crops and varieties or hybrids having tolerance to biotic and abiotic stresses, capacity to replenish soil for sustainable production and express higher yield. Developing suitable cropping systems is an enormous job for achieving potential yield under any agro-climatic conditions [16]. Actually, some factors like resource availability and management are mainly considered to evolve a cropping system.…”
Section: Introductionmentioning
confidence: 99%